Implementation of Atik Model in Developing Early Childhood Cognitive Skills at RA Qurrotul Uyun Bekasi - Emma Rahmani; Sri Watini (Program Studi Pendidikan Islam Anak Usia Dini, Institut Agama Islam Ma'arif (IAIMNU) Metro Lampung, 2024)
Learning activities at an early childhood education institution require creativity and innovation in its implementation. Activities that contain stimulus will provide opportunities for Early Childhood in aspects of cognitive development. Many models exist but not a few are not in accordance with the rules and needs of early childhood. The purpose of this research is that the ATIK Model (Observe-Mimic-Do) is a step that is expected to be used in learning aspects of cognitive development in early childhood. This research uses a qualitative method with a descriptive approach. Data collection techniques were carried out using observations, interviews and documentation in the form of pictures when children were doing learning activities. In conclusion, the ATIK Model carried out as a learning stage helps develop cognitive abilities in early childhood at RA Qurrotul Uyun Bekasi City, the ATIK Model is an option for learning to reach the stages of children's abilities and it is important for teachers to apply the ATIK Model in every lesson.